PERAN KEPEMIMPINAN KEPALA SEKOLAH DALAM MENINGKATKAN MOTIVASI MENGAJAR GURU PENDIDIKAN AGAMA ISLAM: STUDI KUALITATIF NATURALISTIK DI SMA MARTIA BHAKTI BEKASI - Fajar, Fitriah; Supriyanto, Agus (Turats, 2012)
The purpose of this study was to find out the principal's leadership role in increasing the motivation of teachers to teach Islamic Education in High School of Martia Bhakti-Bekasi. This research uses method of naturalistic-qualitative. This method also uses phenomenology and tries to understand the meaning of events and its implications for the research object. From this research we know that principals of leadership have sought to increase the motivation of teachers to teach Islamic Education. The attitude of the principal is very positive, excited, interested, and ready and has the duties and responsibilities as a principal agency to promote education by improving the motivation of teachers to teach Islamic Education